Method for manufacturing electrolytic capacitor
Forming an oxide film on the end surface of the cathode foil in electrolytic capacitors enhances the wettability of the conductive polymer, leading to reduced ESR and increased capacitance, addressing the limitations of conventional capacitors.
Patent Information
- Application Number
- JP2024172441
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-03-25
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-13
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Conventional electrolytic capacitors face challenges in achieving lower Equivalent Series Resistance (ESR) and higher capacitance due to the inability of the conductive polymer to form a homogeneous film that sufficiently covers the dielectric layer between the cathode and anode foils.
The formation of a first oxide film on the end surface of the cathode foil, with a thickness of 0.3 nm to 15 nm, enhances the wettability of the conductive polymer, allowing it to form a more uniform film, thereby reducing ESR and increasing capacitance.
The method results in a significant reduction of ESR and enhancement of capacity extraction effects, improving the productivity of electrolytic capacitors.
Smart Images

Figure 2024174141000001_ABST
Abstract
Description
[Technical Field]
[0001] The present invention relates to an electrolytic capacitor including a capacitor element having a conductive polymer adhered between a cathode foil and an anode foil, and a liquid component such as an electrolyte, and a method for manufacturing the same. [Background technology]
[0002] Electrolytic capacitors are considered promising as small, large-capacity, and low-ESR (equivalent series resistance) capacitors. They include a wound body formed by winding anode foil and cathode foil with a dielectric layer, a capacitor element with a conductive polymer attached to the wound body, and an electrolyte.
[0003] In electrolytic capacitors, a dielectric layer is formed on the surface of the anode foil by chemical conversion, but little research has been done on the chemical conversion of the cathode foil. In Patent Document 1, a solid electrolytic capacitor containing a solid electrolyte made of manganese dioxide is assembled using anode foil and cathode foil that have been subjected to chemical conversion treatment, but there is no mention of forming an oxide film on the end surface of the cathode foil. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-54380 Summary of the Invention [Problem to be solved by the invention]
[0005] Conventional capacitors still have room for improvement in terms of low ESR and high capacitance. This is thought to be because the conductive polymer is not able to form a homogeneous film that sufficiently covers the dielectric layer during the process of adhering the conductive polymer between the cathode foil and the anode foil.
[0006] In view of the above, an object of the present invention is to provide an electrolytic capacitor having reduced ESR and a high capacitance extraction effect, and a method for manufacturing the same. [Means for solving the problem]
[0007] One aspect of the present invention relates to an electrolytic capacitor including a cathode foil, an anode foil having a dielectric layer on a main surface thereof, a conductive polymer covering at least a portion of the dielectric layer between the cathode foil and the anode foil, and a liquid component in contact with the conductive polymer, wherein the cathode foil has a first oxide film on an end surface thereof. Another aspect of the present invention provides an electrolytic capacitor including: a wound body in which an anode foil and a cathode foil are wound with a separator interposed between the anode foil and the cathode foil; a conductive polymer adhered between the anode foil and the cathode foil; and a liquid component in contact with the conductive polymer, an end surface of the cathode foil having a first oxide coating; The electrolytic capacitor has a thickness of the first oxide film of 0.3 nm or more and 15 nm or less.
[0008] Another aspect of the present invention is a method for manufacturing a battery comprising the steps of: forming a wound body including a cathode foil, an anode foil having a dielectric layer on a main surface thereof, and a separator interposed between the cathode foil and the anode foil; forming a capacitor element by depositing a conductive polymer between the cathode foil and the anode foil so as to cover at least a portion of the dielectric layer; impregnating the capacitor element with a liquid component; The method for manufacturing an electrolytic capacitor includes a step of forming a first oxide film on the end surface of the cathode foil before the step of attaching the conductive polymer to the wound body. Another aspect of the present invention is a method for manufacturing a battery, the method comprising: forming a wound body having an anode foil, a cathode foil, and a separator interposed between the anode foil and the cathode foil; a step of impregnating the wound body with a polymer dispersion containing a conductive polymer and a dispersion medium to adhere the conductive polymer to the anode foil and the cathode foil, thereby forming a capacitor element; and impregnating the capacitor element with a liquid component, the method further includes a step of forming an anode end surface oxide film on an end surface of the anode foil after the step of forming a wound body and before the step of attaching the conductive polymer to the wound body, and a step of forming a cathode end surface oxide film that is thinner than the anode end surface oxide film on an end surface of the cathode foil, The present invention relates to a method for manufacturing an electrolytic capacitor, in which the thickness of the oxide film on the cathode end surface is set to 1.5 nm or more and 10 nm or less. Another aspect of the present invention is a method for manufacturing a battery, the method comprising: forming a wound body having an anode foil, a cathode foil, and a separator interposed between the anode foil and the cathode foil; a step of impregnating the wound body with a polymer dispersion containing a conductive polymer and a dispersion medium to adhere the conductive polymer to the anode foil and the cathode foil, thereby forming a capacitor element; and impregnating the capacitor element with a liquid component, the method further includes a step of forming an anode end surface oxide film on an end surface of the anode foil after the step of forming a wound body and before the step of attaching the conductive polymer to the wound body, and a step of forming a cathode end surface oxide film that is thinner than the anode end surface oxide film on an end surface of the cathode foil, The method for manufacturing an electrolytic capacitor includes applying a voltage of 1 V or more and 10 V or less to the cathode foil after the step of forming the wound body to perform chemical conversion treatment, thereby forming the oxide film on the cathode end surface. [Effects of the Invention]
[0009] According to the embodiments of the present invention, in an electrolytic capacitor, the ESR can be significantly reduced and the capacitance extraction effect can be enhanced. [Brief explanation of the drawings]
[0010] [Figure 1] 1 is a cross-sectional view of an electrolytic capacitor according to an embodiment of the present invention; [Figure 2] 2 is a schematic diagram for explaining the configuration of a wound body included in the electrolytic capacitor of FIG. 1. FIG. DETAILED DESCRIPTION OF THE INVENTION
[0011] The electrolytic capacitor according to the present invention includes a cathode foil, an anode foil having a dielectric layer on a main surface thereof, a conductive polymer covering at least a portion of the dielectric layer between the cathode foil and the anode foil, and a liquid component in contact with the conductive polymer. The cathode foil has an oxide film (first oxide film) on an end surface thereof.
[0012] A method for manufacturing an electrolytic capacitor according to an embodiment of the present invention includes the steps of: forming a wound body having a cathode foil, an anode foil having a dielectric layer on a main surface thereof, and a separator interposed between the cathode foil and the anode foil; forming a capacitor element by adhering a conductive polymer between the cathode foil and the anode foil so as to cover at least a portion of the dielectric layer; impregnating the capacitor element with a liquid component; and forming an oxide film (first oxide film) on an end surface of the cathode foil before adhering the conductive polymer to the wound body.
[0013] In this embodiment, we found that forming a first oxide film on the end surface of the cathode foil can improve the ESR reduction effect and enhance the capacitance extraction effect. Although the reason for this is unclear, it is believed that forming a first oxide film on the end surface of the cathode foil significantly enhances the wettability of the cathode foil with the conductive polymer (or a dispersion containing the conductive polymer) when the conductive polymer is applied to the anode foil and cathode foil (or a wound body containing these electrode foils). This enhances the impregnation of the conductive polymer between the anode foil and cathode foil, facilitating the adhesion of the conductive polymer and the formation of an appropriate conductive polymer film. This is believed to result in a low ESR and a high capacitance extraction effect. Furthermore, the improved impregnation of the conductive polymer can shorten the time required to apply the conductive polymer, thereby improving the productivity of electrolytic capacitors.
[0014] The electrolytic capacitor according to this embodiment may have an oxide film (second oxide film) on the main surface of the cathode foil. By forming an oxide film on the main surface as well as on the end surfaces of the cathode foil, the ESR reduction effect and the capacitance extraction effect are further enhanced. In addition, the resistance to reverse voltage is also improved.
[0015] The thickness of the first oxide film formed on the end surface of the cathode foil may be the same as or greater than the thickness of the second oxide film formed on the main surface of the cathode foil. From the viewpoint of suppressing unevenness in the second oxide film and improving the withstand voltage characteristics, it is preferable that the thickness of the first oxide film be smaller than the thickness of the second oxide film.
[0016] The thickness of the first oxide film formed on the end face of the cathode foil is, for example, 0.3 nm to 15 nm, and preferably 0.5 nm to 10 nm. The thickness of the second oxide film formed on the main surface of the cathode foil is, for example, 1.0 nm to 20 nm, and preferably 1.5 nm to 10 nm.
[0017] The thickness of the dielectric layer (second dielectric layer described below) formed on the main surface of the anode foil is preferably greater than the thickness of the second oxide film formed on the main surface of the cathode foil, which makes it easier to ensure high withstand voltage characteristics and suppresses a decrease in capacity.
[0018] The main surfaces of a cathode foil or an anode foil are the two surfaces that occupy the largest areas of the surface of the electrode foil. The end surfaces of a cathode foil or an anode foil are the surfaces at the ends of the electrode foil other than the main surfaces, and include the cut surfaces when a large electrode foil is cut. In a wound body, the surfaces of the electrode foil that are arranged on the top and bottom surfaces other than the peripheral surface are called end surfaces.
[0019] The present embodiment will be described in more detail below with reference to the accompanying drawings, although the present invention is not limited to the following embodiment. FIG. 1 is a cross-sectional view of the electrolytic capacitor according to this embodiment, and FIG. 2 is a schematic view showing a partially developed wound body of the electrolytic capacitor.
[0020] The electrolytic capacitor includes, for example, a capacitor element 10, a bottomed case 11 that houses the capacitor element 10, a sealing member 12 that closes the opening of the bottomed case 11, a seat plate 13 that covers the sealing member 12, lead wires 14A and 14B that extend from the sealing member 12 and pass through the seat plate 13, lead tabs 15A and 15B that connect the lead wires 14A and 14B to the electrodes of the capacitor element 10, and a liquid component (not shown). The capacitor element 10 is housed in the bottomed case 11 together with the liquid component. The vicinity of the open end of the bottomed case 11 is drawn inward, and the open end is curled so as to be crimped to the sealing member 12.
[0021] Capacitor element 10 is fabricated, for example, by attaching a conductive polymer to a wound body as shown in Fig. 2. The wound body includes anode foil 21 having a dielectric layer on at least one main surface, cathode foil 22, and separator 23 interposed therebetween. The conductive polymer is attached between anode foil 21 and cathode foil 22 so as to cover at least a portion of the surface of the dielectric layer of anode foil 21. Capacitor element 10 further includes lead tab 15A connected to anode foil 21 and lead tab 15B connected to cathode foil 22.
[0022] The anode foil 21 and the cathode foil 22 are wound with a separator 23 interposed therebetween. The outermost periphery of the wound body is fixed with a stop tape 24. Note that Fig. 2 shows a partially unfolded state of the wound body before the outermost periphery is fixed.
[0023] Anode foil 21 comprises a metal foil whose surface has been roughened to have an uneven surface, and a dielectric layer is formed on the metal foil having the uneven surface. Cathode foil 22 comprises a metal foil, and may have a first oxide film formed on the end surfaces and a second oxide film formed on the main surfaces.
[0024] Hereinafter, an example of a method for manufacturing an electrolytic capacitor according to this embodiment will be described step by step, and the configuration of the electrolytic capacitor will be described. The cathode foil and the anode foil having a dielectric layer are each prepared prior to the step of forming the wound body. The dielectric layer can be formed by chemical conversion treatment of the anode foil. The chemical conversion treatment of the anode foil is performed in the step of preparing the anode foil, but it may also be performed after the wound body is formed or after the capacitor element is sealed. In addition, the step of forming an oxide film on the cathode foil (chemical conversion treatment) may be performed before the step of attaching a conductive polymer to the wound body. For example, the step of forming an oxide film on the cathode foil may be performed in the step of preparing the cathode foil or in the step of forming the wound body.
[0025] (i) preparing an anode foil 21 having a dielectric layer; First, prepare a metal foil as the raw material for the anode foil 21. Although the type of metal is not particularly limited, it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal, since this facilitates the formation of a dielectric layer.
[0026] Next, the surface of the metal foil is roughened. By roughening, a plurality of projections and depressions are formed on the surface of the metal foil. The roughening is preferably carried out by etching the metal foil. The etching may be carried out by, for example, direct current electrolysis or alternating current electrolysis.
[0027] Next, a dielectric layer is formed on the roughened surface of the metal foil. The formation method is not particularly limited, but it can be formed by chemically treating the metal foil. The chemical treatment forms a dielectric layer on the main surface of the anode foil. At this time, a dielectric layer may also be formed on the end surface of the anode foil. In this specification, the dielectric layer formed on the end surface of the anode foil is also referred to as the first dielectric layer, and the dielectric layer formed on the main surface of the anode foil is also referred to as the second dielectric layer.
[0028] The chemical conversion treatment can be carried out using, for example, a chemical conversion solution. The chemical conversion treatment can be carried out by immersing the metal foil in the chemical conversion solution and then performing a heat treatment. The temperature at this time is, for example, 50 to 85°C. Alternatively, the chemical conversion treatment can be carried out by immersing the metal foil in the chemical conversion solution and applying a voltage. When carrying out the chemical conversion treatment, both a heat treatment and application of a voltage can be carried out.
[0029] Examples of the chemical conversion solution include aqueous solutions containing salts such as phosphates, adipates, and borates. Examples of phosphates include ammonium phosphates, potassium phosphates, and sodium phosphates. Examples of ammonium phosphates include diammonium monohydrogen phosphate and monoammonium dihydrogen phosphate. Examples of adipates and borates include ammonium salts, potassium salts, and sodium salts. The chemical conversion solution may contain one or more of these salts. From the viewpoint of workability, it is preferable to use an ammonium phosphate aqueous solution such as monoammonium dihydrogen phosphate aqueous solution, or an ammonium adipate aqueous solution.
[0030] Typically, for mass production, a large-sized foil (metal foil) such as a valve metal foil is subjected to a surface roughening treatment and a chemical conversion treatment on its main surface. In this case, the treated foil is cut to a desired size to prepare anode foil 21. The cut anode foil 21 has a dielectric layer (second dielectric layer) on its main surface.
[0031] If necessary, after forming a second dielectric layer on the main surface of the anode foil, the anode foil may be cut to a predetermined width and then further subjected to a chemical conversion treatment to form a first dielectric layer on the end surface of the anode foil. To form the first dielectric layer, the anode foil cut to a predetermined width may be immersed in a chemical conversion solution in a rolled state (i.e., with the end surfaces of the anode foil positioned on the top and bottom surfaces of the roll), and heat treatment and / or voltage may be applied. Note that lead terminals may be connected to the anode foil cut to a predetermined width, and then the rolled product may be subjected to a chemical conversion treatment. The temperature for the heat treatment may be selected appropriately from the above range. The anode foil after the chemical conversion treatment may be washed and dried as necessary.
[0032] (ii) Step of preparing cathode foil 22 The cathode foil 22 may be a metal foil, similar to the anode foil 21. Although there are no particular limitations on the type of metal, it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal. If necessary, the surface of the metal foil may be roughened.
[0033] In this step, the metal foil may be subjected to a chemical conversion treatment to form oxide films (first oxide film and second oxide film) on the cathode foil. When performing the chemical conversion treatment in this step, it is preferable to form a second oxide film on the main surface of the cathode foil. In this case, a first oxide film may also be formed on the end surface of the cathode foil.
[0034] The chemical conversion treatment can be carried out, for example, using a chemical conversion solution. The chemical conversion treatment can be carried out by immersing the metal foil in the chemical conversion solution and applying a positive voltage. In this case, the chemical conversion treatment can be carried out, if necessary, at a temperature of, for example, 50 to 85°C (preferably 60 to 75°C).
[0035] The chemical conversion solution can be appropriately selected from those exemplified for the chemical conversion treatment of the anode foil. The voltage applied to the cathode foil during the chemical conversion treatment is, for example, 1 to 10 V, and preferably 2 to 5 V. When the applied voltage is in this range, an oxide film (particularly, the second oxide film) of appropriate thickness is easily formed, which is advantageous from the viewpoint of increasing capacity. By adjusting the magnitude of the applied voltage during the chemical conversion treatment, the thickness of the oxide film (particularly, the second oxide film) can be adjusted.
[0036] From the viewpoint of mass production, a large foil (metal foil) of a valve metal or the like is usually subjected to a surface roughening treatment or a chemical conversion treatment, and the treated foil is then cut to a desired size to prepare a cathode foil.
[0037] Alternatively, after forming the second oxide film on the main surfaces of the cathode foil, the cathode foil may be cut to a predetermined width and then further subjected to a chemical conversion treatment to form a first oxide film on the end surfaces of the cathode foil. To form the first oxide film, the cathode foil cut to a predetermined width may be immersed in a chemical conversion solution in a rolled state (i.e., with the end surfaces of the cathode foil positioned on the top and bottom surfaces of the roll) and a voltage may be applied. The applied voltage and temperature conditions may be appropriately selected from the above-mentioned ranges. Alternatively, the cathode foil cut to a predetermined width may be connected to lead terminals and then rolled up and then subjected to a chemical conversion treatment. The cathode foil after the chemical conversion treatment may be washed and dried as necessary.
[0038] (iii) forming a wound body Next, a wound body is produced using the anode foil 21 and the cathode foil 22. First, anode foil 21 and cathode foil 22 are wound with separator 23 interposed therebetween. At this time, lead tabs 15A and 15B are wound in while being wound, so that lead tabs 15A and 15B can be planted upright from the wound body as shown in FIG.
[0039] The material of the separator 23 can be, for example, a nonwoven fabric whose main component is synthetic cellulose, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, vinylon, nylon, aromatic polyamide, polyimide, polyamideimide, polyetherimide, rayon, or glass.
[0040] The material of the lead tabs 15A and 15B is not particularly limited as long as it is a conductive material. The material of the lead wires 14A and 14B connected to the lead tabs 15A and 15B, respectively, is also not particularly limited as long as it is a conductive material.
[0041] Next, among the wound anode foil 21, cathode foil 22 and separator 23, a stop tape 24 is placed on the outer surface of cathode foil 22, which is the outermost layer, and the end of cathode foil 22 is fixed with stop tape 24.
[0042] In this step, the wound body may be subjected to chemical conversion treatment (re-chemical conversion treatment) to form at least a part of the dielectric layer on the anode foil, and at least a part of the oxide film (first oxide film, second oxide film) on the cathode foil.
[0043] In particular, when the anode foil 21 is prepared by cutting a large metal foil in step (i), the wound body is further subjected to chemical conversion treatment (re-chemical conversion treatment) to form a dielectric layer (first dielectric layer) on the end surface of the anode foil 21. The chemical conversion treatment can also be performed using a chemical conversion solution. The chemical conversion treatment may be performed, for example, by immersing the wound body in the chemical conversion solution and then performing a heat treatment. Alternatively, the chemical conversion treatment may be performed by immersing a third electrode in the chemical conversion solution together with the wound body and applying a positive voltage to the anode foil of the wound body with the third electrode as the counter electrode. Both heat treatment and voltage application may be performed. The conditions for the chemical conversion treatment can be determined appropriately from those described for step (i).
[0044] When the cathode foil is subjected to chemical conversion treatment in this step, for example, a third electrode is immersed in the chemical conversion solution together with the wound body, and a positive voltage is applied to the wound cathode foil with the third electrode as the counter electrode to oxidize the surface. The voltage applied to the cathode foil is, for example, 0.2 to 10 V, preferably 0.5 to 5 V, relative to the third electrode. When the first oxide film is preferentially formed on the end surfaces of the cathode foil, the third electrode may be placed opposite the top and / or bottom surfaces of the wound body, and a voltage may be applied to the cathode foil. The chemical conversion solution can be determined as appropriate from those described for step (i), and the temperature for the chemical conversion treatment can be determined as appropriate from those described for step (ii).
[0045] When the first oxide film is preferentially formed, applying a voltage equal to or lower than the voltage applied when forming the second oxide film (specifically, when forming the second oxide film in step (ii)) can prevent by-product gas from adhering to the already formed second oxide film, thereby preventing unevenness in the second oxide film. This can prevent a decrease in the withstand voltage characteristics. Note that instead of using a third electrode, a voltage may be applied to the cathode foil using the anode foil as a counter electrode.
[0046] The chemical conversion treatment may be performed with the entire wound body immersed in the chemical conversion solution, or with at least the top and bottom surfaces of the wound body immersed in the chemical conversion solution. When the cathode foil is converted by the latter method, the oxide film tends to be formed in a concentrated manner on the edge surfaces of the cathode foil, which is advantageous in terms of increasing the thickness of the first oxide film. After the chemical conversion treatment, the wound body is washed and dried as necessary.
[0047] (iv) A step of attaching a conductive polymer to the wound body In this step, a treatment solution containing a conductive polymer is applied to the wound body to adhere the conductive polymer to the wound body. Between the anode foil 21 and the cathode foil 22, the conductive polymer may be adhered in the form of a film to the surface of the dielectric layer (first dielectric layer, second dielectric layer) of the anode foil 21 to form a conductive polymer layer (or solid electrolyte layer), but this is not limited to this. The conductive polymer may be adhered so as to cover at least a portion of the first oxide film and / or the second oxide film of the cathode foil 22. The conductive polymer may also cover at least a portion of the surface of the separator 23.
[0048] The conductive polymer is preferably polypyrrole, polythiophene, polyaniline, etc. These may be used alone, in combination of two or more kinds, or as a copolymer of two or more kinds of monomers. The weight-average molecular weight of the conductive polymer is not particularly limited, but is, for example, 1,000 to 100,000.
[0049] In this specification, polypyrrole, polythiophene, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyaniline, etc. as their basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes poly(3,4-ethylenedioxythiophene) (PEDOT), etc.
[0050] A dopant may be added to the conductive polymer. From the viewpoint of suppressing dedoping from the conductive polymer, it is desirable to use a polymer dopant. Examples of polymer dopants include anions of polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic sulfonic acid, polymethacrylic sulfonic acid, poly(2-acrylamido-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These may be used alone or in combination of two or more. Furthermore, these may be homopolymers or copolymers of two or more monomers. Among these, polystyrene sulfonic acid (PSS) is preferred.
[0051] The weight average molecular weight of the dopant is not particularly limited, but is preferably, for example, 1,000 to 100,000 in terms of facilitating the formation of a homogeneous solid electrolyte layer.
[0052] The conductive polymer may be attached to the wound body by applying a solution containing a monomer, a dopant, an oxidizing agent, etc. to the wound body and then chemically or electrolytically polymerizing the solution in situ. Alternatively, the conductive polymer may be attached to the wound body by applying a treatment liquid containing the conductive polymer (hereinafter simply referred to as a polymer dispersion) to the wound body.
[0053] The concentration of the conductive polymer contained in the polymer dispersion is preferably 0.5 to 10% by mass. The average particle size D50 of the conductive polymer is preferably, for example, 0.01 to 0.5 μm. Here, the average particle size D50 is the median diameter in the volume particle size distribution determined by a particle size distribution analyzer using the dynamic light scattering method.
[0054] The polymer dispersion contains a liquid dispersion medium and a conductive polymer dispersed in the liquid dispersion medium. The polymer dispersion may be a solution in which the conductive polymer is dissolved in the liquid dispersion medium, or a dispersion in which conductive polymer particles are dispersed in the liquid dispersion medium. After the treatment liquid is impregnated into the wound body, the wound body is usually dried to volatilize at least a portion of the liquid dispersion medium.
[0055] To prevent the conductive polymer from being de-doped, an acid may be dissolved in the liquid dispersion medium. Preferred examples of the acid include phthalic acid, benzoic acid, nitrobenzoic acid, salicylic acid, trimellitic acid, and pyromellitic acid.
[0056] The polymer dispersion can be obtained, for example, by dispersing a conductive polymer in a liquid dispersion medium or by polymerizing a precursor monomer in the liquid dispersion medium to generate conductive polymer particles. A preferred polymer dispersion contains, for example, poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonate (PSS), i.e., PEDOT / PSS. An antioxidant for the conductive polymer may be added, but since PEDOT / PSS is hardly oxidized, it is not necessary to use an antioxidant.
[0057] The liquid dispersion medium may be water, a mixture of water and a non-aqueous solvent, or a non-aqueous solvent. The non-aqueous solvent is not particularly limited, and for example, a protic solvent or an aprotic solvent can be used. Examples of protic solvents include alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, and propylene glycol, and ethers such as formaldehyde and 1,4-dioxane. Examples of aprotic solvents include amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, and ketones such as methyl ethyl ketone.
[0058] A simple and preferred method for applying (impregnating) the polymer dispersion to the wound body is, for example, immersing the wound body in the polymer dispersion contained in a container. Alternatively, ultrasonic vibrations may be applied to the wound body or the polymer dispersion while immersed in the polymer dispersion. After the wound body is removed from the polymer dispersion, drying is preferably performed at a temperature of, for example, 50 to 300°C. The steps of applying the polymer dispersion to the wound body and drying the wound body may be repeated two or more times. By performing these steps multiple times, the coverage of the conductive polymer on the wound body can be increased.
[0059] This completes the capacitor element 10, in which the conductive polymer is attached between the anode foil 21 and the cathode foil 22. The conductive polymer formed on the surface of the dielectric layer actually functions as a cathode material.
[0060] (v) A step of impregnating the capacitor element 10 with a liquid component Next, the capacitor element 10 is impregnated with a liquid component. This results in an electrolytic capacitor with an excellent dielectric layer repair function. The method for impregnating the capacitor element 10 with the liquid component is not particularly limited. For example, a simple and preferable method is to immerse the capacitor element 10 in the liquid component contained in a container. The impregnation is preferably carried out under reduced pressure, for example, in an atmosphere of 10 to 100 kPa.
[0061] The liquid component may be a non-aqueous solvent or a mixture (i.e., an electrolyte) of a non-aqueous solvent and an ionic substance (solute, e.g., an organic salt) dissolved therein. The non-aqueous solvent may be an organic solvent or an ionic liquid. High-boiling point solvents are preferred as non-aqueous solvents. Examples of suitable non-aqueous solvents include polyhydric alcohols such as ethylene glycol and propylene glycol, cyclic sulfones such as sulfolane (SL), lactones such as γ-butyrolactone (γBL), amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, carbonate compounds such as propylene carbonate (PC), ethers such as 1,4-dioxane, ketones such as methyl ethyl ketone, and formaldehyde. An organic salt is a salt in which at least one of the anion and cation contains an organic substance. Examples of organic salts that may be used include trimethylamine maleate, triethylamine borodisalicylate, ethyldimethylamine phthalate, mono-1,2,3,4-tetramethylimidazolinium phthalate, and mono-1,3-dimethyl-2-ethylimidazolinium phthalate.
[0062] (vi) Sealing the capacitor element 10 Next, capacitor element 10 is sealed. Specifically, capacitor element 10 is first housed in bottomed case 11 so that lead wires 14A and 14B are located on the open upper surface of bottomed case 11. Bottomed case 11 can be made of a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.
[0063] Next, sealing member 12, which is formed so that lead wires 14A and 14B pass through it, is placed above capacitor element 10, and capacitor element 10 is sealed in bottomed case 11. Next, a horizontal drawing process is performed near the open end of bottomed case 11, and the open end is crimped to sealing member 12 to form a curl. Then, seat plate 13 is placed on the curled portion, completing the electrolytic capacitor as shown in FIG. 1. Thereafter, an aging process may be performed while applying a rated voltage.
[0064] The sealing member 12 is made of an elastic material containing a rubber component. Examples of the rubber component that can be used include butyl rubber (IIR), nitrile rubber (NBR), ethylene propylene rubber, ethylene propylene diene rubber (EPDM), chloroprene rubber (CR), isoprene rubber (IR), Hypalon rubber, silicone rubber, and fluororubber. The sealing member 12 may contain fillers such as carbon black and silica.
[0065] After sealing the capacitor element 10, a chemical conversion treatment may be further performed to form a first oxide film and a dielectric layer. The chemical conversion treatment may be performed using an electrolytic solution. For example, the chemical conversion treatment may be performed by applying a positive voltage to the anode foil and the cathode foil while the capacitor element 10 is immersed in the electrolytic solution. In this case, a heat treatment is usually also performed. The temperature for the heat treatment is, for example, 100 to 150°C. If the cathode foil is subjected to the chemical conversion treatment after sealing the capacitor element 10, the resistance to reverse voltage can be increased.
[0066] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, such as chip-type electrolytic capacitors that use a metal sintered body as an anode body, and stacked-type electrolytic capacitors that use a metal plate as an anode body. [Example]
[0067] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.
[0068] Example 1 In this example, a wound electrolytic capacitor (diameter 6.3 mm×length 5.8 mm) with a rated voltage of 35 V and a rated capacitance of 47 μF was fabricated. A specific method for fabricating the electrolytic capacitor will be described below.
[0069] (Preparing the anode foil) An Al foil with a thickness of 120 μm was prepared. This Al foil was subjected to a DC etching treatment to roughen the surface. Next, the Al foil was subjected to a chemical conversion treatment to form a dielectric layer (thickness: approximately 70 nm), thereby obtaining an anode foil. The dielectric layer was formed by immersing the Al foil in an ammonium adipate solution and performing a chemical conversion treatment at 70°C for 30 minutes while applying a voltage of 50 V to the Al foil. The anode foil was then cut to a predetermined size to prepare the anode foil.
[0070] (Preparation of cathode foil) An Al foil having a thickness of 50 μm was subjected to an etching treatment to roughen the surface of the Al foil. Next, the Al foil was subjected to a chemical conversion treatment to form an oxide film (mainly a second oxide film). The oxide film was formed by immersing the Al foil in an ammonium adipate solution and performing the chemical conversion treatment at 70°C for 30 minutes while applying a voltage of 3 V to the Al foil. The Al foil was then cut to prepare cathode foils.
[0071] (Production of wound body) An anode lead tab and a cathode lead tab, each connected to a lead wire, were connected to the anode foil and the cathode foil, respectively, and the anode foil and the cathode foil were wound with the lead tabs in between, with a separator interposed therebetween, and the outer surfaces were fixed with a winding tape to produce a wound body.
[0072] The prepared wound body was immersed in an ammonium adipate solution, and a voltage of 50 V was applied to the anode foil while performing chemical conversion treatment again at 70°C for 60 minutes, thereby forming a dielectric layer on the end surface of the anode foil.
[0073] Next, while the wound body was immersed in an ammonium adipate aqueous solution, a voltage of 3 V was applied to the cathode foil to form a first oxide film on the end surface of the cathode foil. The thickness of the first oxide film was 3 nm, and the thickness of the second oxide film formed on the main surface of the cathode foil was 5 nm.
[0074] (Preparation of polymer dispersion) A mixed solution was prepared by dissolving 3,4-ethylenedioxythiophene and polystyrene sulfonic acid as a dopant in ion-exchanged water. Iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added to the resulting mixed solution while stirring, and a polymerization reaction was carried out. After the reaction, the resulting reaction solution was dialyzed to remove unreacted monomers and excess oxidant, yielding a polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of polystyrene sulfonic acid.
[0075] (Fabrication of capacitor elements) The wound body was immersed in a polymer dispersion contained in a designated container in a reduced pressure atmosphere (40 kPa) for 5 minutes, and then removed from the polymer dispersion. The wound body impregnated with the polymer dispersion was then dried in a drying oven at 150°C for 20 minutes, allowing the conductive polymer to adhere between the anode and cathode foils of the wound body. In this way, a capacitor element was completed.
[0076] (Electrolyte impregnation) The capacitor element was impregnated with an electrolyte solution in a reduced pressure atmosphere (40 kPa) using a solution containing PEG, γBL, SL, and mono(ethyldimethylamine) phthalate (solute) in a mass ratio of 25:25:25:25.
[0077] (Sealing of capacitor elements) The capacitor element impregnated with the electrolyte was sealed to complete the electrolytic capacitor, which was then subjected to aging treatment at 130°C for 2 hours while applying the rated voltage.
[0078] The electrostatic capacitance and ESR value of the obtained electrolytic capacitor were determined by the following procedure. Using an LCR meter for four-terminal measurement, the capacitance (initial capacitance) (μF) of the electrolytic capacitor was measured at a frequency of 120 Hz. Using a four-terminal LCR meter, the ESR value (initial ESR value) (mΩ) of the electrolytic capacitor was measured at a frequency of 100 kHz. The capacitance and ESR values were measured for 120 randomly selected electrolytic capacitors, and the average values were calculated.
[0079] Comparative Example 1 After forming a dielectric layer on the end surface of the anode foil of the wound body, a polymer dispersion was applied to the end surface of the cathode foil without forming a first oxide film on the end surface of the cathode foil. Except for this, an electrolytic capacitor was fabricated and evaluated in the same manner as in Example 1. The results of the Examples and Comparative Examples are shown in Table 1. Example 1 is A1, and Comparative Example 1 is B1.
[0080] [Table 1]
[0081] As shown in Table 1, the electrolytic capacitor of the example in which the first oxide film was formed on the end surface of the cathode foil had a lower ESR and a higher capacitance than the electrolytic capacitor of the comparative example in which the first oxide film was not formed. [Industrial Applicability]
[0082] The present invention can be used in a so-called hybrid electrolytic capacitor that includes a conductive polymer adhered between an anode foil and a cathode foil, and a liquid component such as an electrolyte solution. [Explanation of symbols]
[0083] 10: Capacitor element, 11: Bottomed case, 12: Sealing member, 13: Seat plate, 14A, 14B: Lead wires, 15A, 15B: Lead tabs, 21: Anode foil, 22: Cathode foil, 23: Separator, 24: Winding tape
Claims
1. forming a wound body having an anode foil, a cathode foil, and a separator interposed between the anode foil and the cathode foil; impregnating the wound body with a polymer dispersion containing a conductive polymer and a dispersion medium to adhere the conductive polymer to the anode foil and the cathode foil to form a capacitor element; impregnating the capacitor element with a liquid component; forming an anode end surface oxide film on an end surface of the anode foil after the step of forming a wound body and before the step of attaching the conductive polymer to the wound body; and forming a cathode end surface oxide film that is thinner than the anode end surface oxide film on an end surface of the cathode foil, The method for producing an electrolytic capacitor, wherein the thickness of the oxide film on the cathode end surface is 1.5 nm or more and 10 nm or less.
2. 2. The method for producing an electrolytic capacitor according to claim 1, wherein the cathode end surface oxide film is formed by applying a voltage of 1 V or more and 10 V or less to the cathode foil after the step of forming the winding body to perform a chemical conversion treatment.
3. forming a wound body having an anode foil, a cathode foil, and a separator interposed between the anode foil and the cathode foil; impregnating the wound body with a polymer dispersion containing a conductive polymer and a dispersion medium to adhere the conductive polymer to the anode foil and the cathode foil to form a capacitor element; impregnating the capacitor element with a liquid component; the step of forming an anode end surface oxide film on an end surface of the anode foil after the step of forming a wound body and before the step of attaching the conductive polymer to the wound body; and the step of forming a cathode end surface oxide film that is thinner than the anode end surface oxide film on an end surface of the cathode foil, the cathode foil after the step of forming the winding body is subjected to a chemical conversion treatment by applying a voltage of 1 V or more and 10 V or less to form the cathode end surface oxide film.
Citation Information
Patent Citations
Solid electrolytic capacitor and its manufacturing method
JP2006222333A
Electrolytic capacitor, and method of manufacturing the same
JP2010074089A
Solid electrolytic capacitor
JP2013093539A
Solid electrolytic capacitor and housing for solid electrolytic capacitor
WO2014163204A1
Solid electrolytic capacitor
JP1999054380A
